Multi-responsive photo- and chemo-electrical single-molecule switches - Darwish, Nadim; Aragonès, A.; Darwish, T.; Ciampi, S.; Díez-Pérez, I. (American Chemical Society, 2014)
Incorporating molecular switches as the active components in nanoscale electrical devices represents a current challenge in molecular electronics. It demands key requirements that need to be simultaneously addressed including fast responses to external stimuli and stable attachment of the molecules to the electrodes while mimicking the operation of conventional electronic components. Here, we report a single-molecule switching device that responds electrically to optical and chemical stimuli. A light pointer or a chemical signal can rapidly and reversibly induce the isomerization of bifunctional spiropyran derivatives in the bulk reservoir and, consequently, switch the electrical conductivity of the single-molecule device between a low and a high level. The spiropyran derivatives employed are chemically functionalized such that they can respond in fast but practical time scales. The unique multistimuli response and the synthetic versatility to control the switching schemes of this single-molecule device suggest spiropyran derivatives as key candidates for molecular circuitry.